Nebulized 3% Hypertonic Saline Reduces the Duration of Hospital Stay in Comparison to Nebulized Adrenaline in the Treatment of Acute Bronchiolitis (East West Medical College Journal, 2026)
Background: In case of infents and young chidren acute bronchiolitis is the most common lower respiratory tract infection. The respiratory syncytial virus is the most common cause of bronchiolitis. Recently the role of nebulized 3% saline has come into focus. As an another treatment option nebulized adrenaline has also been suggested, its primary role being the reduction of mucosal edema, which is an important part of the disease pathology in bronchiolitis. Objective: To see the clinical recovery and duration of hospital stay of nebulized adrenaline in comparison to nebulized 3% hypertonic saline in the treatment of acute bronchiolitis. Methods: This study was a randomized controlled trial, carried out in the Department of Pediatrics, East West Medical College and Hospital from October 2022 to September 2024. A total of 70 children from 1 month to 2 years of age of either sex who were diagnosed and admitted with acute bronchiolitis were enrolled. After enrollment, they were randomly assigned to 3% nebulized hypertonic saline (group A=35) and nebulized adrenaline-1:1000 group (group B=35). Monitoring was done by respiratory distress assessment instrument (RDAI) score at 12 hours interval for 1st 24 hours and then 24 hourly till the time of patient discharge. The efficacy was determined by assessing clinical severity score/RDAI score and length of hospital stay. Data were analyzed using SPSS version-23. Results: The mean age was found 6.34±3.89 months in group A and incase of group B 6.06±3.55 months. The majority of patients were males in both groups. All patients had a cough, breathing difficulty, Ronchi, and chest indrawing in both groups. Changes in heart rate were 5.68±6.61/min in group A and 2.86±5.87/min in group B, which was significantly decreasing in group A than in group B. Mean clinical severity scores at 12 hours and at 24 hours were statistically significant (p